A study of the types and manifestations of physicians' unintended behaviors in the DRG payment system - Chang, Wei-Fu; Yan, Xin-Yu; Ling, Hao; Liu, Ting; Luo, Ai-Jing (Frontiers in Public Health, 2023)
In recent years, China has implemented the Diagnosis Related Groups (DRG) payment system as part of its healthcare insurance reimbursement policy. Numerous studies have focused on the effectiveness of DRG payment system in controlling unreasonable growth in medical expenses. However, there has been no systematic report on the types of unintended behaviors exhibited by doctors under the DRG payment system. By combining interrupted time series regression and semi-structured interviews, this study discovered that doctors engage in unintended behaviors within the framework of the DRG payment system. In the early implementation of the DRG payment system in China, the contradictions between the flawed DRG payment methods and supporting systems and the actual diagnostic and treatment work manifested in the form of unintended doctor behaviors. Most of these unintended behaviors can be considered reasonable feedback from doctors to cope with the existing system flaws. They are conducive to identifying the deficiencies in China's DRG payment system and suggesting directions for improvement.